A combinatorial strategy of alternative promoter use during differentiation of a heterocystous cyanobacterium. Issue 4 (27th June 2017) - Muro‐Pastor, Alicia M.; Brenes‐Álvarez, Manuel; Vioque, Agustín
Summary: Heterocystous cyanobacteria such as Nostoc sp. are filamentous photosynthetic organisms that, in response to nitrogen deficiency, undergo a differentiation process transforming certain, semi‐regularly spaced cells into heterocysts, devoted to nitrogen fixation. During transition to a nitrogen‐fixing regime, growth of most vegetative cells in the filament is temporarily arrested due to nutritional deprivation, but developing heterocysts require intense transcriptional activity. Therefore, the coexistence of arrested vegetative cells and actively developing prospective heterocysts relies on the simultaneous operation of somewhat opposite transcriptional programs. We have identified genes with multiple nitrogen‐responsive transcriptional starts appearing in seemingly paradoxical combinations. For instance, sigA, encoding the RNA polymerase housekeeping sigma factor, is transcribed from one major nitrogen stress‐repressed promoter and from a second, nitrogen stress‐induced promoter. Here, we show that both promoters are expressed with complementary temporal dynamics. Using a gfp reporter we also show that transcription from the inducible promoter takes place exclusively in differentiating heterocysts and is already detected before any morphological or fluorescence signature of differentiation is observed. Tandem promoters with opposite dynamics could operate a compensatory mechanism in which repression of transcription from the major promoter operative in vegetative cells is offset by transcription from a new promoter only in developing heterocyst.